KONSEP JIHAD DALAM AL-QUR’AN: Studi Penafsiran Ayat-Ayat Jihad dalam Tafsīr al-Munīr - Saepul Hidayat (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2023)
This article is about the concept of jihad in the Qur'an in the view of Wahbah az-Zuhaili through the book Tafsīr Al-Munīr Aqidah, Shari'ah, Manḣaj. The concept of jihad has always been a theme of pros and cons in the history of Muslim thought, so there needs to be a more in-depth and relevant study along with developments. What's more, many interpret jihad with the meaning of war. Wahbah is a contemporary scholar who has a broad mind and always offers solutions to various problems of the people. In addition, the book Tafsīr Al-Munīr was written with the spirit of the times and shed light on various issues of the times, especially the problem of jihad in society. It is with the spirit of the times and the breadth of thinking that makes this research a new study on important matters. This research will explain how the concept of jihad and how the interpretation of Wahbah related to the verses of jihad in the Qur'an. The method used in this research is character thematic and descriptive-analytical. So the conclusion of this research is that jihad has a diverse meaning and is not fixed in the meaning of war, even though in the verses of the Qur'an there is a meaning that leads to war. But that is a form of defense not attack.